Toward a knowledge‐based theory of the firm - Grant, Robert M. (Strategic Management Journal, 1996)
Abstract Given assumptions about the characteristics of knowledge and the knowledge requirements of production, the firm is conceptualized as an institution for integrating knowledge. The primary contribution of the paper is in exploring the coordination mechanisms through which firms integrate the specialist knowledge of their members. In contrast to earlier literature, knowledge is viewed as residing within the individual, and the primary role of the organization is knowledge application rather than knowledge creation. The resulting theory has implications for the basis of organizational capability, the principles of organization design (in particular, the analysis of hierarchy and the distribution of decision‐making authority), and the determinants of the horizontal and vertical boundaries of the firm. More generally, the knowledge‐based approach sheds new light upon current organizational innovations and trends and has far‐reaching implications for management practice.